2016
DOI: 10.1189/jlb.4a1015-483r
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT regulation of Aspergillus fumigatus corneal infections and IL-6/23-stimulated neutrophil, IL-17, elastase, and MMP9 activity

Abstract: IL-6 and IL-23 (IL-6/23) induce IL-17A (IL-17) production by a subpopulation of murine and human neutrophils, resulting in autocrine IL-17 activation, enhanced production of reactive oxygen species, and increased fungal killing. As IL-6 and IL-23 receptors trigger JAK1, -3/STAT3 and JAK2/STAT3 phosphorylation, respectively, we examined the role of this pathway in a murine model of fungal keratitis and also examined neutrophil elastase and gelatinase (matrix metalloproteinase 9) activity by IL-6/23-stimulated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 57 publications
0
46
1
1
Order By: Relevance
“…Since studies reporting neutrophil positivity to IL‐17A continue to be published, ignoring either the previously mentioned information, or the few works showing the contrary, recently we decided to perform additional investigations . Using multiple methodological approaches (RT‐qPCR, ChIP‐seq, ELISA, intracellular staining and immunoblotting), we could confirm that highly purified populations of human neutrophils, either resting, or activated by a variety of stimulatory conditions, such as TLR and dectin ligands, fungal PAMPs and cytokines, including 20 μg/mL IL‐6 plus 2 μg/mL IL‐23, neither express IL‐17A, IL‐17F, IL‐17B, IL‐17C, IL‐17D and IL‐17E mRNA, nor produce IL‐17A, IL‐17F, IL‐17A/F and IL‐17B in vitro .…”
Section: The Case Of Il‐17 Expression In Human Neutrophilsmentioning
confidence: 98%
See 2 more Smart Citations
“…Since studies reporting neutrophil positivity to IL‐17A continue to be published, ignoring either the previously mentioned information, or the few works showing the contrary, recently we decided to perform additional investigations . Using multiple methodological approaches (RT‐qPCR, ChIP‐seq, ELISA, intracellular staining and immunoblotting), we could confirm that highly purified populations of human neutrophils, either resting, or activated by a variety of stimulatory conditions, such as TLR and dectin ligands, fungal PAMPs and cytokines, including 20 μg/mL IL‐6 plus 2 μg/mL IL‐23, neither express IL‐17A, IL‐17F, IL‐17B, IL‐17C, IL‐17D and IL‐17E mRNA, nor produce IL‐17A, IL‐17F, IL‐17A/F and IL‐17B in vitro .…”
Section: The Case Of Il‐17 Expression In Human Neutrophilsmentioning
confidence: 98%
“…41 Similarly, 4 different groups 40,[42][43][44][45] have shown that IL-6 plus IL-23 efficiently induce IL-17A, IL-17F and IL-17RC mRNA expression and protein production by human neutrophils. Curiously, 2 of these groups have specified that concentrations lesser than 20 lg/mL IL-6 plus 2 lg/mL for IL-23 are not effective in terms of IL-17A induction, [42][43][44] while another group found 20 ng/mL IL-6 and/or 20 ng/mL IL-23 as perfectly functional in neutrophils from asthmatic subjects, 45 as well as up to 100 ng/ mL in control neutrophils. Whatever the case is, the most numerous evidence for the expression of IL-17 by human neutrophils derives from IHC and/or IF studies documenting IL-17A + -neutrophils in tissue specimens from a variety of pathological conditions (see Table 1).…”
Section: Expression In Human Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have now extended this role to the eye, as neutrophils have been identified as a critical source of IL-17A during fungal keratitis [53] . Assessment of JAK/ STAT pathway inhibition in this model was shown to have a negative effect on ROS production and fungal killing activity, but also blocked the activity of elastase and gelatinase that is associated with tissue damage [54] . CD4 and γδ T cells may also produce IL-17A after A. fumigatus challenge.…”
Section: Il-17a Il-22 and Gm-csfmentioning
confidence: 99%
“…S tat3 -defective human neutrophils inhibit the growth of A. fumigatus swollen conidia and germlings and have normal chemotactic activity [60], consistent with the model that invasive aspergillosis susceptibility in these patients stems from anatomic lung defects associated with recurrent bacterial infections. Ruxolitinib, a small molecule JAK/STAT inhibitor, reduced Aspergillus killing by IL-6-stimulated and IL23-stimulated human neutrophils [61]. These data support the notion that JAK/STAT signaling contributes to neutrophil-mediated Aspergillus clearance though the precise mechanisms remain to be defined.…”
Section: Fungal Recognition and Innate Immune Activationmentioning
confidence: 55%